Reflection of Gender Norms in Kyrgyz and Turkish Tales on Social Life - Ayşe Güler Küçükturan; Hatice Selcen Aslan (Sakarya University, 2024)
The messages on gender roles given through fairy tales, which contain elements related to the structure of society, cause children to internalize the knowledge and behavioral patterns they have acquired since their early ages, to be exhibited at later ages. This study was carried out to scrutinize the gender norms in Kyrgyz and Turkish fairy tales, revealing their similarities and differences, and examining the reflection of these norms on social life. A case study model, one of the qualitative research methods, was used and data was collected through document review and interview techniques. The documents (fables), used in the study, were determined using the stratified purposeful sampling method. Among the tales reached in the first stage, the ones in the realistic tale type and enriched with extraordinary elements were selected: a Kyrgyz and a Turkish tale with a family theme were selected from these tales. Tales were examined in terms of the gender norms they contain. The contents of the tales were analyzed in detail with the descriptive analysis technique. Individual interviews were conducted with 2 Kyrgyz students living in Türkiye and 2 Turkish students living in Kyrgyzstan, and the data were analyzed with the descriptive analysis technique. In the research, different gender norms in both tales were determined and it was concluded that these norms were reflected in social life. These norms have emerged in the form of supporting the patriarchal structure in the Turkish fairy tale while in the Kyrgyz fairy tale, the woman is considered to be precious.